Physiological Responses and Tolerance of Halophyte Sesuvium portulacastrum L. to Cesium - Ganesh C. Nikalje; Manoj Shrivastava; T. D. Nikam; Penna Suprasanna (Advances in Agriculture)
Cesium (Cs) is a soil contaminant and toxic to the ecosystem, especially the plant species. In this study, we have assessed the potential of a halophyte Sesuvium portulacastrum for its Cs tolerance and accumulation. Thirty days old S. portulacastrum plants were subjected to different concentrations of Cs (0, 5, 10, 25, 50, and 150 mg·L−1 Cs) using cesium chloride. The biomass and photosynthetic pigments were not affected up to 25 mg·L−1 Cs treatment while a significant decline in pigment levels was observed at higher concentrations. The Cs treatments increased protein content at low concentrations while higher concentrations were inhibitory. Under Cs exposure, significant induction of antioxidant enzymes such as ascorbate peroxidase (APX), catalase (CAT), glutathione reductase (GR), and superoxide dismutase (SOD) was observed. The antioxidant enzyme activities were upregulated up to 50 mg·L−1 Cs but decreased significantly at 150 mg·L−1. The accumulation of Cs was dose and tissue-dependent as evidenced by a higher accumulation of Cs in leaves (536.10 μg·g−1) as compared to stem (413.74 μg·g−1) and roots (284.69 μg·g−1). The results suggest that S. portulacastrum is a hyper-accumulator of Cs and could be useful for the phytoremediation of Cs-contaminated soils.